Dose-dependent effects of chronic lead toxicity in vivo: Focusing on trace elements and gut microbiota. (August 2022) - Yu, Leilei; Duan, Hui; Yu, Yaqi; Zhang, Qingsong; Zhao, Jianxin; Zhang, Hao; Zhai, Qixiao; Tian, Fengwei; Chen, Wei
Abstract: Dose-dependent effects of chronic Pb exposure-induced injuries, especially on the trace elements and gut microbiota in mice, have not been explored. In the present study, we investigated these aspects using C57BL/6 mouse models that were exposed to Pb via drinking water with Pb concentrations of 0.1, 0.5, and 1.0 g/L for 8 weeks. The results showed that with the increase in chronic Pb exposure dose, the Pb levels in the blood and tissues, Zn levels in the kidney and brain were elevated, and the levels of bone Zn, kidney Fe, brain Mg, Ca, and Fe, renal catalase activity, and glutathione levels, as well as the expression of colonic zonula occludens-1 and occludin, decreased with a strong linear correlation. Moreover, the relative abundance of Marvinbryantia and Ruminococcus 1 increased, while that of Lactobacillus and Roseburia decreased linearly with the Pb exposure dose. PICRUSt analysis revealed that chronic Pb exposure had a greater impact on the metabolism of macronutrients, trace elements, and neurodegenerative injury. These findings suggest that chronic Pb exposure disrupts trace element levels in tissues, especially in the brain, and induces gut dysbiosis in a dose-dependent manner, which is different from the dose-effect of acute Pb toxicity. Graphical abstract: Image 1 Highlights: Pb-induced trace elements imbalance are related to the disorder of gut microbiota. Pb changed the Fe and Zn levels in the brain and kidney in a dose-dependent manner. Pb-induced changes in abundance of special gut microbiota are dose-dependent. Pb reduced the expression of ZO-1 and Occludin in a dose-dependent manner.